A DEPOSIT OF ROMAN AMPHORAE IN PULA (CROATIA): A preliminary report - Starac, Alka (Rei Cretariae Romanae Fautorum Acta, 2024)
During the ten-month rescue archaeological rescue project in the urban core of Pula in 2005, a deposit containing 1889 amphorae set in the drainage layer was discovered. A smaller section of the same deposit was discovered during the construction of the Austrian-Hungarian infantry barracks in 1873. Part of the deposit found in the 19th century is kept in the Archaeological Museum of Istria in Pula, while a larger part is displayed beneath the substructure of the amphitheatre. The amphorae were stacked on different levels in divided building spaces, arranged in one or more tiers, one above other. Generally, the amphorae filled the whole space in each void and were set almost all entire and turned upside down. Many of them after setting up were intentionally pierced near the toe. One pair of amphorae was pierced by uniformly distributed holes in the form of a sieve before being set into the deposit: the holes were pierced by blows from a sharp object after the vessels had ceased to serve their original function.